[Literature of the supernatural worlds beyond reason] - Center for Humanities ([Mount Kisko, N.Y.] The Center [producer], 1960)
Explores some of our questions and feelings about the mysterious, nonrational aspects of the universe. The literary works examine the human desire for knowledge and power that transcends the boundaries of time, space, reason and life itself.
VHS
Felta Book Sales [distributor], Makati, Metro Manila.
Keywords: Supernatural in literature; Supernatural -- Literary collections